A new species of Mysella from Patagonia (Bivalvia: Galeommatoidea) - Ituarte, Cristian Federico (2012)
The poorly known diversity of the genus Mysella in the southwestern Atlantic is improved with the description of a new species from San Julian Bay, Santa Cruz Province, Argentina. Mysella patagona new species is characterized by the relative large, strikingly subquadrate, slightly inequilateral and flat shell; a cleft hinge plate, with two widely diverging teeth in the right valve, and a cylindrical internal ligament located in a deep ligamental pit. From the anatomical point of view, M. patagona new species is characterized by the presence of inner and outer demibranchs, with very few interlamellar junctions. The marked subquadrate shell outline easily distinguishes M. patagona from any other Mysella species currently known from the Magellan Region.